The Conquest of New France; A Chronicle of the Colonial Wars - Wrong, George McKinnon, 1860-1948; Johnson, Allen, 1870-1931 (Salt Lake City, UT : Project Gutenberg, 2002)
"The Conquest of New France; A Chronicle of the Colonial Wars" by George M. Wrong is a historical account written in the early 20th century. The work narrates the colonial wars between France and England in North America, focusing on the struggles for control over territories during the 17th and early 18th centuries. The story primarily revolves around key figures such as Louis de Buade, Comte de Frontenac, and the impact of his leadership amidst escalating conflicts, illustrating the complex dynamics of colonial powers and their interactions with Native American tribes. At the start of the book, the author sets the stage by discussing the long-standing animosity between France and England, which extends into their colonial ventures in North America. The introduction details the early confrontations, highlighting Frontenac's tumultuous governance in Canada and his contentious relationship with English settlers and the Iroquois. It also outlines the motivations behind the colonial powers' expansionist ambitions while painting a vivid picture of the challenges posed by the harsh wilderness and the existing indigenous populations. Through a blend of historical narrative and character exploration, the opening portion establishes the intricate tapestry of power struggles over land and the clash of cultures that define this era of American history. (This is an automatically generated summary.)
Release date is 2002-02-01
Keywords: United States -- History -- Colonial period, ca. 1600-1775; Canada -- History -- To 1763 (New France); United States -- History -- French and Indian War, 1754-1763; United States -- History -- Queen Anne's War, 1702-1713; United States -- History -- King William's War, 1689-1697; United States -- History -- King George's War, 1744-1748